2017
DOI: 10.1080/13854046.2017.1394493
|View full text |Cite
|
Sign up to set email alerts
|

Prospective memory impairment in idiopathic REM sleep behavior disorder

Abstract: We show evidence for a differential pattern of PM impairment in iRBD with severe impairment of event-based and concurrent preservation of time-based PM. We theorize that event-based PM impairment in iRBD is caused by severe impairment of retention and recognition mechanisms in episodic memory whereas time-based PM seems to be affected by reduced striatal dopaminergic synapses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…NREM and REM processes may interact dynamically to help preserve a range of cognitive processes [74]. In the current work, REM sleep duration was significantly associated with prospective memory consolidation in young adults and middle-to-older aged adults, which adds to a developing literature on prospective memory being impacted by sleep disruption [9][10][11][12][75][76][77] and by clinical sleep disorders [78][79][80]. The current findings fit the theoretical view that prospective memory consolidation occurs via reactivation processes followed by cue-intention association processes, but alternative accounts should also be tested.…”
Section: Discussionmentioning
confidence: 62%
“…NREM and REM processes may interact dynamically to help preserve a range of cognitive processes [74]. In the current work, REM sleep duration was significantly associated with prospective memory consolidation in young adults and middle-to-older aged adults, which adds to a developing literature on prospective memory being impacted by sleep disruption [9][10][11][12][75][76][77] and by clinical sleep disorders [78][79][80]. The current findings fit the theoretical view that prospective memory consolidation occurs via reactivation processes followed by cue-intention association processes, but alternative accounts should also be tested.…”
Section: Discussionmentioning
confidence: 62%
“…Significant differences in cognitive functioning (memory, executive functions) between iRBD and healthy controls have been found ( 83 86 ). The frequency of mild cognitive impairment (MCI) was estimated to be 33–50% in iRBD patients and 63–73% in PD patients with RBD, respectively ( 87 ).…”
Section: Diagnostic Accuracy Of Clinical Measures For Predicting Convmentioning
confidence: 99%
“…In iRBD selective attention, executive functions and episodic verbal and non-verbal memory are the most affected ( 83 85 , 92 ). Positive correlation between time-based prospective memory performance and reduced striatal dopamine transport uptake on DaT scan on the more affected side has been found ( 86 ), indicating that impaired prospective memory may also be a marker for neurodegeneration associated with dopamine depletion syndromes. However, the presence of visuospatial and visuoconstructional deficits has also been reported in some studies ( 92 – 94 ), especially in those iRBD subgroups that later convert to PD dementia or DLB.…”
Section: Diagnostic Accuracy Of Clinical Measures For Predicting Convmentioning
confidence: 99%
“…[ 58 59 ] Recent studies have shown that event-related memory and prospective memory were impaired in patients with iRBD. [ 60 ] A study involving 21 iRBD patients, 26 PD patients, and 26 healthy controls found that the accuracy of visual short-term memory was significantly reduced in patients with iRBD and PD, suggesting that there was a similarity in working memory impairments between them. [ 55 ] Even some studies found that iRBD patients were more likely to have impaired word memory and visual space function regardless of whether they had PD,[ 61 ] and iRBD without dementia also had a progressive decline in memory and executive functions.…”
Section: Iagnosis Of R Apid Ementioning
confidence: 99%